Measuring Impunity in Latin America: Conceptual and Methodological Challenges - Juan Antonio Le Clercq; Azucena Cháidez; Gerardo Rodríguez (Íconos)
Impunity is increasingly being recognized as a phenomenon that is at once often both the cause and effect of some of the most serious problems in Latin America as well as in other parts of the world. This article examines some of the conceptual and methodological challenges involved in measuring the phenomenon of impunity, with a particular focus on Latin America. The analysis presented in this article also examines the correlation between impunity and other problems governments face, such as insecurity, violence, corruption and inequality. Finally, we examine the methodology of the 2015 Global Impunity Index that is a useful tool for analyzing these phenomena.